Optimization of Production Costs in Overburden and Coal Removal Activities Using Linear Programming Method - Aryanti Virtanti Anas; Syarif Hanfil; Rizki Amalia (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2026)
The problem that occurred at the research site was an increase in production targets in 2025, which caused the company to add heavy equipment units, directly impacting production costs, which needed to be minimized. This study aims to optimize production costs and analyze the impact of variable changes on the results of production cost optimization. The method used to obtain optimal costs is linear programming, utilizing the simplex approach with the aid of POM for Windows software. The optimization results show a decrease in production costs from IDR5,356,889,868.58 ≈ IDR5,356,889,869 to IDR4,893,240,018.56 ≈ IDR4,893,240,019 per month, or a savings of IDR463,649,850.02 ≈ IDR463,649,850 per month, with a reduction of 9%, through a reduction in the number of working days without lowering production targets. Sensitivity analysis indicates that production constraints are the most influential factor on the optimal solution, while all decision variables play an active role. Some other constraints still have remaining capacity, indicating that the generated solution is efficient and optimal. The application of the linear programming method to minimize production costs has proven to achieve optimal production costs through the reduction of working days for each unit of loading and unloading equipment and transport equipment, and the variable most influencing the optimal solution is the production constraint.